Rethinking the politics of writing differently through écriture féminine. Issue 1 (February 2019) - Vachhani, Sheena J.
This article examines the writing practices most often associated with French feminist thought called écriture féminine and subjects it to debates concerning embodied writing in management and organisation studies. Écriture féminine explores the intersections between language, sexual difference and writing from the body. Often considered a distinct and alluring strand of feminist writing and philosophy, I draw together possibilities for its use and explore implications that emerge for teaching and researching management and organisations. With focus on two modes of writing the feminine, through Luce Irigaray and Hélène Cixous, the intersections between sex/text are examined and form ways of decentring conventional modes of writing. The article concludes with discussing the politics of writing differently for researching, teaching and writing about organisations, the need to expose the effects of a masculine singularity in writing and how it may suppress and conceal possibilities but also offer opportunities for claiming space for an affective feminist politics inscribed in language.